Analyzing Early Childhood Development (ECD) in Yangon and rural Ayeyarwady: October - November 2023 - Tauseef, Salauddin; Headey, Derek D.; Oo, Theingi; Linn, Khin Mar (International Food Policy Research Institute, 2025)
KEY FINDINGS • Support for learning: 79 percent of children received four or more stimulating activities, but only 20 percent had three or more books; fathers’ engagement with children (30 percent) lags behind mothers (81 percent). • Caregiver Reported Early Development Instruments (CREDI): the standardized score in the study sample was 58.4, which is lower than scores reported in similar studies from India (70.0), Tanzania (64.0), and Armenia (81.8) • Household inequalities: Asset-rich, food-secure households show higher ECD scores; severe food insecurity lowers scores by ~2 points. • Conflict and shocks: Migration and physical insecurity reduce ECD scores by 0.5-1.0 points. • Parental influences: Fathers’ education boosts ECD outcomes; maternal depression and low aspirations for girls reduce ECD outcomes. • Care quality: Inadequate care reduces ECD scores by 1.3 points; stunting lowers ECD scores by 0.8 points, while access to books and ECE increases ECD scores by 0.7 points.